2005
DOI: 10.1126/science.1103717
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of the Plasmodium Life Cycle by Genomic, Transcriptomic, and Proteomic Analyses

Abstract: Plasmodium berghei and Plasmodium chabaudi are widely used model malaria species. Comparison of their genomes, integrated with proteomic and microarray data, with the genomes of Plasmodium falciparum and Plasmodium yoelii revealed a conserved core of 4500 Plasmodium genes in the central regions of the 14 chromosomes and highlighted genes evolving rapidly because of stage-specific selective pressures. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
677
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 756 publications
(720 citation statements)
references
References 27 publications
37
677
4
2
Order By: Relevance
“…This finding agrees with most expression studies in Plasmodium spp., which consistently find abundant L3 transcripts and protein in liver (39,40) and iRBC stages (41). Although low abundance L3 transcripts were detected in sporozoites (42,43), L3 protein was undetectable (44) or nearly undetectable (42,43) by mass spectrometry compared with later timepoints. L3 is a reported discrete malaria CD8 + T-cell epitope carried on BALB/c malaria-infected erythrocytes; a few additional epitopes were reported in C57BL/6 mice (45).…”
Section: Hts Reveals Greater Ctl Diversity Following Different Sporozmentioning
confidence: 64%
“…This finding agrees with most expression studies in Plasmodium spp., which consistently find abundant L3 transcripts and protein in liver (39,40) and iRBC stages (41). Although low abundance L3 transcripts were detected in sporozoites (42,43), L3 protein was undetectable (44) or nearly undetectable (42,43) by mass spectrometry compared with later timepoints. L3 is a reported discrete malaria CD8 + T-cell epitope carried on BALB/c malaria-infected erythrocytes; a few additional epitopes were reported in C57BL/6 mice (45).…”
Section: Hts Reveals Greater Ctl Diversity Following Different Sporozmentioning
confidence: 64%
“…While transcriptome and proteome analyses indicate that some genes are regulated post-transcriptionally [8,9], other genes are regulated at the level of transcription. For example, analyses of 5' end upstream regions of the asexual and sexual stages have been shown by transfection studies that they function as promoters by supporting reporter gene expression [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, almost 15% of annotated genes show transcription of antisense RNAs in the asexual stages [7]. Finally, results from genomewide transcription analyses and bioinformatics studies show that compared to the yeast genome, the Plasmodium genome has an under-representation of DNA-binding proteins and transcription factors and over-representation of RNA-binding proteins [8] Recent data that compares transcriptome and proteome profiles in different stages of the parasite life cycle has revealed that post-transcriptional regulation via RNA-binding proteins may be a major mechanism of regulating gene expression in gametocytes and sexual stages [9]. These accumulating data suggest that there may be novel mechanisms of gene regulation in the malaria parasite, including mRNA stabilization, antisense RNA and ncRNA-mediated regulation.…”
Section: Introductionmentioning
confidence: 99%